The Influence of Accreditation, Promotion, and Brand Image on Enrollment Interest, Moderated by Cost, at Universities in Serang City - Iman Hickmatullah; Dhany Isnaeni Dharmawan (Harmony Management: International Journal of Management Science and Business, 2025)
This study aims to analyze the influence of students' perceptions of Accreditation (X1), Promotion (X2), and Brand Image (X3) on their Interest (Y) in registering, with Cost (Z) serving as a moderating variable. Data were collected from 399 respondents. The validity test results indicate that all research instruments are valid. Meanwhile, the reliability test results show that all variables have Cronbach's Alpha values ranging from "Good" to "Excellent," confirming their reliability. The study's findings reveal that Promotion and Cost are dominant factors with a positive and significant influence on interest in registering. Additionally, Accreditation also has a positive and significant effect on interest. In contrast, the Brand Image variable does not have a significant partial influence on interest. However, when considered simultaneously, Accreditation, Promotion, and Brand Image collectively have a significant impact on interest. The moderation test results demonstrate that Cost significantly moderates the relationship between Brand Image and Interest, indicating that the effect of Brand Image on interest is either strengthened or weakened by cost considerations. In conclusion, to attract prospective students, private universities should prioritize effective promotional strategies and manage perceptions of competitive costs, including the availability of scholarships. While brand image remains important, focusing on tangible benefits reinforced by cost factors will have a greater impact on prospective students' decisions.